RITES FUNERAIRES ODJOUKROU DE LA RECONCILIATION: UNE INSTITUTION TRADITIONNELLE DE L’ΕB-KOK ET SES CHANGEMENTS - Raymond, Mel Mèlèdje (European Scientific Journal, ESJ, 2014)
Odjoukrou of yesterday and today have the same funeral ideology: the life; so that the dead man has to enter it beyond or God’s paradise, reconciled and in peace with the alive and the deaths. But, those of today, more modern westernized and Christian, find the funeral rites of reconciliation of yesterday based on the witchcraft. Yet, the latter is not only disputed by the new religions, but found demonic and source of conflicts by the modern societies. Nevertheless, Odjoukrou finds that they do not feel living confidentially the Christian funeral rites which are proposed to them. Then, let us hope that the inculturation of the Gospel (at the Catholics) which is at present current in the odjoukrou country, will bend over this aspect of the question.